Exploring the potential for growth and trade in fruit and oilseed-to-edible oils value chains following political shifts in Zimbabwe - Shingie Chisoro-Dube; Cornelius Dube; Wellington Matsika (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Zimbabwe's persistent economic challenges since the early 1990s have been largely attributed to unpopular political decisions at the expense of building productive capacity in different sectors of the economy. Using a global value chains framework taking into account political economy dynamics, this article explores how developments in the political space shape the opportunities for upgrading in different sectors of the economy. Using a case study approach relying on data from interviews with industry stakeholders in Zimbabwe, this paper identifies existing capabilities and potential areas for upgrading in production, processing, and exports in the fruit and oilseed-to-edible oils value chains in the context of recent political shifts in Zimbabwe. The fruit and oilseeds-to-edible oils value chains were selected particularly because of the underlying productive capabilities in agriculture and food processing, which provide the potential to drive substantial recovery and employment to meet local, regional, and international demand.
Keywords: L52; L66; O13; O14; 330; agriculture; edible oils; oilseeds; processing; production; trade; value chain